Mature B‐NHL in children, adolescents and young adults: current therapeutic approach and emerging treatment strategies. (6th January 2019) - Egan, Grace; Goldman, Stan; Alexander, Sarah
Summary: Mature B cell lymphomas account for approximately 60% of all cases of non‐Hodgkin lymphoma (NHL) in children and adolescents and includes Burkitt lymphoma (BL), diffuse large B cell lymphoma (DLBCL) and other less common histologies. The outcome for patients treated with modern regimens in resource‐intensive settings is excellent. Improvements in care have been accomplished through enhanced supportive therapy, including tumour lysis management and incremental refinement of chemotherapy backbones via cooperative group clinical trials in which patients receive risk group‐specific intensive chemotherapy. More recent trials have established the safety and efficacy of immunotherapy. Ongoing work is required to address the substantial burden of acute therapy‐related toxicity, as well as the identification of effective therapies for those patients with relapsed and refractory disease, for whom outcomes remain very poor. In this review we will summarize the results from recent therapeutic clinical trials, describe the evidence to support the inclusion of rituximab and review the rationale for the investigation of several new categories of novel agents for mature B cell lymphomas in children and adolescents.